Treatment of recurrent bronchial carcinoma: the role of high-dose-rate endoluminal brachytherapy - Hauswald, Henrik; Stoiber, Eva Maria; Rochet, Nathalie; Lindel, Katja; Grehn, Christian J.; Becker, Heinrich D.; Debus, Jürgen; Harms, Wolfgang (International journal of radiation oncology, biology, physics, 2010)
Purpose - This study's aim was to assess outcome and toxicity of high-dose-rate endoluminal brachytherapy (HDREB) for recurrent bronchial carcinoma. - Methods and Materials - From 1987 to 2005, 41 patients were treated with HDREB for symptomatic recurrent bronchial carcinoma. All patients had previously undergone external beam radiotherapy (EBRT) with a median dose of 56 Gy (range, 30-70 Gy). The median HDREB dose applied was 15 Gy (range, 5-29 Gy). The median time interval between primary EBRT and reirradiation was 9 months (range, 2-54 months). - Results - After a median follow-up of 6.7 months, the 6-, 12-, and 24-month overall survival rates were 58%, 18%, and 7%, respectively. The median overall survival time was 6.7 months. Local remission was achieved in 73% of patients (n = 30). A total of 24% of patients (n = 10) showed no response or progressive disease within 8 weeks after treatment. In 1 patient, treatment response was not documented. The 6-, 12-, and 24-month local control rates were 38%, 17%, and 3%, respectively. The median local progression-free survival time was 4 months (range, 1-23 months). Prognostic factors were a total dose of ≥15 Gy of HDREB (p = 0.029) and a Karnofsky performance score of ≥80% (p = 0.0012). The cause of death was locoregional progression in 27% of patients (n = 11), distant metastases in 24% of patients (n = 10), fatal hemorrhage in 15% of patients (n = 6), and other causes in 29% of patients (n = 12). None of the patients with locally controlled disease showed grade 3 or 4 late effects. - Conclusions - Palliative treatment of symptomatic, locally recurrent bronchial carcinoma with HDREB can effectively relieve symptoms in the majority of patients while causing only few complications. Still, time to progression is short.
Gesehen am 11.04.2023